Ultrasound-Assisted Leaching and Kinetic Study of Blended Copper Slag - Turan, M. Deniz; Sari, Z. Abidin; Demiraslan, Aslihan (Springer, 2019)
This article deals with the dissolution of blended copper slag (flash and converter furnace) in hydrogen peroxide and acetic acid in the presence of ultrasound. The parameters that are effective on leaching efficiency, such as leaching temperature, leaching time, ultrasound power, acetic acid concentration, and hydrogen peroxide concentration, were investigated. The optimum leaching conditions for maximum copper dissolution (93 pct) and minimum iron dissolution (3 pct) were determined as follows: 2 M H2O2, 4 M CH3COOH, 10 pct of ultrasound power, 65 degrees C of leaching temperature, 60 minutes of leaching time, and 1:25 of solid-liquid ratio. According to the Brunauer-Emmett-Teller (BET) analysis results on the original sample and leaching residue, the ultrasound caused formation of microcracks on the particle surface; however, the BET surface area increased and the mean adsorption pore width decreased. The apparent activation energy was found to be 55.35 kJ/mol, and the kinetics equations of the processes were established.
Keywords: Hydrogen-Peroxide; Converter Slag; Sulfuric-Acid; Concentrate; Extraction; Metals